Marketing innovation for higher education a bibliometric analysis using the VOS viewer application - Khairusy, Mirza Abdi; Gaffar, Vanessa; Karsikah, Karsikah; Suprayogi, Yogi; Ardie Putra, Alfian Prayana; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
The purpose of this research is to carry out a bibliometric analysis of marketing innovation in higher education using VOSviewer. This study uses a quantitative description method. The data used in this study are search results based on the keyword